Electrochemical Decarboxylative Cyclization of α‐Amino‐Oxy Acids to Access Phenanthridine Derivatives. Issue 6 (1st February 2022) - Zhan, Yanling; Dai, Changhui; Zhu, Zitong; Liu, Ping; Sun, Peipei
Abstract: Phenanthridines are a class of useful heterocycles in the field of drug development. In this work, a method via electrochemical decarboxylative cyclization of α‐amino‐oxy acids to access phenanthridine derivatives was developed. This reaction proceeded through iminyl radical formation cascade intramolecular cyclization from readily available materials under environmentally friendly conditions. A wide range of phenanthridine derivatives were obtained in moderate to high yields. Abstract : Phenanthridines are an important class of heterocyclic compounds found in pharmaceuticals and natural products. Herein, an efficient electrochemical decarboxylative cyclization of α‐amino‐oxy acids to synthesize phenanthridine derivatives was developed. This reaction proceeded through iminyl radical formation cascade intramolecular cyclization from readily available materials under transition‐metal‐free and mild conditions.